신유물론 시대의 문학 읽기 - 유선무 (안과밖:영미문학연구, 2020)
This essay aims to examine the recent revival of materialist ontology, known as new materialism, and to evaluate its role in invigorating the literary studies and critical theory. In its attempt to explore materiality and physicality beyond the linguistic turn and social constructionist frameworks, this critical trend tries to overcome anthropocentrism and natural-culture dualism supposedly inherent in the previous critical theory. Correctly claiming that “matter” has been an underexplored question, new materialists call our attention to matter's agential, formative, and self-organizing power. However, in a parallel way in which some constructivists collapse all material into language, some radical new materialists are committing an error of collapsing all language into materiality. Karen Barad's notion of co-constitutive “intra-actions” between cognition and matter is an attempt to move beyond the constructivistnew materialist impasse, which will contribute to open up a new line of investigation more attuned to the affective, critical, and semiautonomous power of a literary text. The future of literary studies, viewed from the new materialist perspective, depends not only on how matter does things with us but how we do things with matter. Granted that matter retains obstinate opacity, human ethics and epistemology is not something we can easily get rid of. Literature enables us to become equipped with more, not less, “response-ability,” curbing human arrogance which makes man think that he can freely endow agential power on non-human entities and that he can occupy a completely neutral position among things without his human ethical and epistemological biases.
Keywords: New Materialism; Literary Studies; Anthropocentrism; “Intra-actions” Karen Barad; “response-ability”